Pengembangan Media Pembelajaran Berbasis Android Menggunakan Smart Apps Creator pada Mata Pelajaran Informatika Materi Perangkat Keras Komputer Kelas X - Hasyim Asy’ari; Dewi Rosita (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to develop and validate the feasibility of android-based learning media using smart apps creator on computer hardware material for high school students in grade X. Conventional learning processes are often less interesting and not optimal in conveying hardware concepts that tend to be abstract. Therefore, the development of this interactive media is expected to be an alternative in learning media in class and outside the classroom. This study uses the Research and Development (R&D) method with the PPE model consisting of three stages, namely Planning, Production and Evaluation. The research stages include defining student needs and curriculum, media design, developing smart apps creator learning media products, and distributing and evaluating feasibility. The validation results were tested and assessed by 3 media validation experts, 1 material validation expert. The assessment results from media experts obtained an average value of 64.3 so that it is included in the